Bacillus subtilis Protects Public Goods by Extending Kin Discrimination to Closely Related Species - Nicholas A. Lyons (American Society for Microbiology, 2017)
ABSTRACT Kin discrimination systems are found in numerous communal contexts like multicellularity and are theorized to prevent exploitation of cooperative behaviors. The kin discrimination system in Bacillus subtilis differs from most other such systems because it excludes nonkin cells rather than including kin cells. Because nonkin are the target of the system, B. subtilis can potentially distinguish degrees of nonkin relatedness, not just kin versus nonkin. We examined this by testing a large strain collection of diverse Bacillus species against B. subtilis in different multicellular contexts. The effects of kin discrimination extend to nearby species, as the other subtilis clade species were treated with the same antagonism as nonkin. Species in the less-related pumilus clade started to display varied phenotypes but were mostly still discriminated against, while cereus clade members and beyond were no longer subject to kin discrimination. Seeking a reason why other species are perceived as antagonistic nonkin, we tested the ability of B. subtilis to steal communally produced surfactant from these species. We found that the species treated as nonkin were the only ones that made a surfactant that B. subtilis could utilize and that nonkin antagonism prevented such stealing when the two strains were mixed. The nonkin exclusion kin discrimination method thus allows effective protection of the cooperative behaviors prevalent in multicellularity while still permitting interactions with more distant species that are not a threat. IMPORTANCE Multicellular systems like bacterial biofilms and swarms rely on cooperative behaviors that could be undermined by exploitative invaders. Discriminating kin from nonkin is one way to help guard against such exploitation but has thus far been examined only intraspecifically, so the phylogenetic range of this important trait is unknown. We tested whether Bacillus subtilis treats other species as nonkin by testing a single strain against a diverse collection of Bacillus isolates. We found that the species in the same clade were treated as nonkin, which then lessened in more distant relatives. Further experiments showed that these nonkin species produced a cooperative good that could be stolen by B. subtilis and that treating each other as nonkin largely prevented this exploitation. These results impact our understanding of interspecies interactions, as bacterial populations can interact only after they have diverged enough to no longer be a threat to their cooperative existences.